Taxonomic notes on Leandra (Melastomataceae, Miconieae) - II - Reginato, Marcelo; Goldenberg, Renato (Phytotaxa, 2018)
(Taxonomic notes on Leandra (Melastomataceae, Miconieae) - II). In this study we propose 12 synonyms, 15 lectotypes and a new name for eastern Brazilian species of Leandra. Leandra pubescens var. tomentosa is placed in the synonymy of Clidemia atrata; Leandra laxa in the synonymy of L. eriocalyx; Leandra sessiliflora in the synonym of L. glabrata; Leandra longisetosa in the synonymy of L. multiplinervis; Leandra balduinii, L. pauloensis and L. schwackei in the synonymy of L. regnellii; Leandra linearifolia and L. parvifolia in the synonymy of L. salicina; Leandra pubescens var. pubescens in the synonymy of L. strigilliflora; Leandra gardneriana and L. depauperata in the synonymy of L. xantholasia. We propose lectotypes for C. atrata, L. depauperata, L. gardneriana, L. glabrata, L. laxa, L. linearifolia, L. longisetosa, L. multiplinervis, L. parvifolia, L. pauloensis, L. pubescens var. pubescens, L. pubescens var. tomentosa, L. regnellii, L. sessiliflora, and L. xantholasia. A new name is proposed to correct a mistake recently made in the taxonomic revision of Leandra sect. Leandra.